Missional communities : the rise of the post-congregational church - McNeal, Reggie (San Francisco : Jossey-Bass, 2011)
"The third book in the trilogy that explores the popular missional movementFrom Reggie McNeal, the bestselling author of The Present Future and Missional Renaissance, comes the third book in the series that helps to define and illuminate the popular missional movement. This newest book in the trilogy examines a natural outgrowth of the move toward a missional orientation: the deconstruction of congregations into very small Christian communities. For all those thousands of churches and leaders who have followed Reggie McNeal's bold lead, this book details the rise of a new life form in churches. Discusses how to move a church from an internal to an external ministry focus Reggie McNeal is a recognized leader in the missional movement Outlines an alternative to the program church model that is focused on the projects and passions of the congregants This book draws on McNeal's twenty years of leadership roles in local congregations and his work over the last decade with thousands of clergy and church leaders"--
"Let there be ... missional communities" -- The missional church conversation -- Missional communities---European style -- Soma communities : missional communities as organizing architecture -- Campus renewal UT : missional communities as campus evangelism strategy -- Future travelers : missional communities as megachurch strategy -- Mission Houston : missional communities for spiritual formation and community transformation -- Looking ahead.
Includes index.
"A Leadership Network publication."
Keywords: Church development, New; Church; Church renewal; Postmodernism -- Religious aspects -- Christianity; Christianity -- Forecasting